Artificial Intelligence in Foreign Language Teaching: A Tool or a Teacher’s Replacement? - Akhmadullina Alina Ildarovna (Academia One Publishing, 2025)
The integration of Artificial Intelligence (AI) in language education has revolutionized traditional teaching and learning approaches. This article explores the pedagogical implications of AI-driven tools, including automated writing evaluation, AI chatbots, and intelligent tutoring systems, in second language acquisition. It highlights the benefits of AI, such as personalized feedback, enhanced learner engagement, and adaptive learning pathways, while also addressing ethical concerns related to data security and the diminishing role of human interaction. By analyzing recent research and case studies, this study provides insights into how AI can complement human instruction, fostering a hybrid learning environment that balances technological advancements with essential communicative and cognitive skills. The findings underscore the need for a thoughtful integration of AI in language education to maximize its potential while mitigating its challenges.
Keywords: AI; Foreign Language Teaching; Language Acquisition